Sustainable Wages and Need for Convergence in EU-28 Countries - Andrei, Jean; Marian, Zaharia; Rodica Manuela, Gogonea; Dan Cosmin, Petrache; Radu, Zaharia (Industrija, 2017)
In context of recent transformation of the EU economic and social model, assuring sustainable wages for workers represents a great challenge. The effects of economic crisis have imposed numerous shifts in productivity frontier and labor productivity. Despite the fact that the wage`s level have been improved recently, the need for adjustments is still more actual. The main aim of this paper is to analyze if the wage level is sustainable and it assures a proper living standard in accordance to EU-28 economic and social model. In addition, a model of wages evolution is described.
Keywords: Annual net earnings; Convergence; Cluster analysis; Productivity; Economics; Wages